Interdisciplinary video review: Assessing milestones and providing feedback. (September 2019) - Delbridge, Emilee J; Wilson, Tanya; McGregor, James D; Ankerman, Jared S
Literature within residency education states that directly observing resident–patient visits with the goal of providing formative and summative feedback to learners is helpful for resident skill development. However, limited literature exists regarding what specifically is most effective to observe and evaluate. Furthermore, the perspectives of learners are not always taken into consideration in the development and implementation of direct observation or video review of resident–patient encounters. This article overviews some of the current literature relevant to family medicine training and provides a description of some of the changes in one residency's use of recorded encounters. Suggestions are provided for future steps for family medicine residencies to effectively utilize video review.